2007
DOI: 10.1109/tgrs.2007.900681
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Classification of Buried Unexploded Ordnance Using Nonparametric Prior Models

Abstract: Abstract-We used kernel density estimation (KDE) methods to build a priori probability density functions (pdfs) for the vector of features that are used to classify unexploded ordnance items given electromagnetic-induction sensor data. This a priori information is then used to develop a new suite of estimation and classification algorithms. As opposed to the commonly used maximumlikelihood parameter estimation methods, here we employ a maximum a posteriori (MAP) estimation algorithm that makes use of KDE-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 41 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…We have demonstrated that this type of classification works well even when the model assumptions (e.g. distance from transmitter) are violated (Aliamiri et al, 2007). …”
Section: Simplified Modeling Of Mcsem Responsesmentioning
confidence: 86%
See 3 more Smart Citations
“…We have demonstrated that this type of classification works well even when the model assumptions (e.g. distance from transmitter) are violated (Aliamiri et al, 2007). …”
Section: Simplified Modeling Of Mcsem Responsesmentioning
confidence: 86%
“…Comparing these pole values to a library provides a means of classifying unknown targets (Aliamiri et al, 2007). We have demonstrated that this type of classification works well even when the model assumptions (e.g.…”
Section: Simplified Modeling Of Mcsem Responsesmentioning
confidence: 98%
See 2 more Smart Citations
“…Initially we took the time decay of the total NSMS over 25 time channels for all targets and parameterized it using the Pasion-Oldenburg law of equation (57). Taking the logarithm of that equation we arrive at the linear model…”
Section: Mixed Model Approach Applied To Camp Sibert Datamentioning
confidence: 99%